2020
DOI: 10.1007/s11157-020-09525-1
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic fungi: unconventional applications

Abstract: Entomopathogenic fungi (EPF) are microorganisms that cause fatal diseases of arthropods. The infection process involves several stages that consist of direct contact of the fungus with the surface of the cuticle of the attacked insect. The factors that determine the effectiveness of the infection process include lytic enzymes, secondary metabolites, and adhesins produced by EPF. Because of their high insecticidal effectiveness, these fungi are commonly used as biopesticides in organic farming. As the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(110 citation statements)
references
References 115 publications
(173 reference statements)
0
78
1
7
Order By: Relevance
“…Acetamiprid at the highest dose acted slightly faster, while at the end of the experiment it turned out that the highest mortality was achieved for the combined action of spores and acetamiprid. Similarly to chemical insecticides, entomopathogens do not kill insects immediately and their lethal effect is delayed even up to 14 days [13]. When a combination of spores and acetamiprid was used, an effect similar to that achieved by the insecticide applied alone was observed.…”
Section: Influence Of Acetamiprid Spores Of M Brunneum Arsef2107 Anmentioning
confidence: 97%
See 1 more Smart Citation
“…Acetamiprid at the highest dose acted slightly faster, while at the end of the experiment it turned out that the highest mortality was achieved for the combined action of spores and acetamiprid. Similarly to chemical insecticides, entomopathogens do not kill insects immediately and their lethal effect is delayed even up to 14 days [13]. When a combination of spores and acetamiprid was used, an effect similar to that achieved by the insecticide applied alone was observed.…”
Section: Influence Of Acetamiprid Spores Of M Brunneum Arsef2107 Anmentioning
confidence: 97%
“…It is suggested that in attacked insects, dtxs induce paralysis and muscle contraction via muscle depolarization by the direct opening of Ca 2+ channels in the membrane [10,11]. Besides their insecticidal activity, dtxs have also potential as pharmaceuticals showing antiviral, antitumor, cytotoxic, immunosuppressant or antiproliferative effects [12,13]. However, due to the endophytic properties of Metarhizium sp., the presence of dtxs can be found in, e.g., potatoes [14], maize and strawberries [15], causing dtxs to enter the food chain and pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…fungi, was unconventional applications (Litwin et al 2020)of the biological control options in controlling cockroaches. It has several advantages such as affordable cost, high yield, and not interfere the environment with the residue (Mantzoukas and Eliopoulos 2020).…”
Section: Entomopathogenicmentioning
confidence: 99%
“…It colonizes the hemocoel consuming the nutrients of the hemolymph as well as secreting toxins that contribute to the modification of its structural integrity by inhibiting the selective process or its enzymes besides interfering with its regulatory system accelerating the death of the insect. Once the insect is dead, the cuticle is breached again from the inside out in order to emerge conidiophores that sporulate on the body of the insect and can begin the infection in other arthropods by spreading the spores (Borges et al, 2010;Mascarin & Jaronski, 2016;Valero-Jiménez et al, 2016;Daza et al, 2019;Litwin et al, 2020) The production of specific pigments confer to the spores resistance to ultraviolet radiation, and to environmental conditions that could be detrimental to the fungus (Chintapenta et al, 2014). The infection process lasts up to 14 days and depending on the fungal species the first symptoms of infection occur 7 days after the first contact of the fungus with the insect (Litwin et al, 2020).…”
Section: General Overview On the Pathogenesis Of Beauveria Bassianamentioning
confidence: 99%